Combining Gender, Work, and Family Identities: The Cross-Over and Spill-Over of Gender Norms into Young Adults’ Work and Family Aspirations - Meeussen, Loes; Veldman, Jenny; Van Laar, Colette (Frontiers in Psychology, 2016)
The current study investigates how descriptive and prescriptive gender norms that communicate work and family identities to be (in)compatible with gender identities limit or enhance young men and women’s family and career aspirations. Results show that young adults (N=445) perceived gender norms to assign greater compatibility between female and family identities and male and work identities than vice versa, and that young men and women mirror their aspirations to this traditional division of tasks. Spill-over effects of norms across life domains and cross-over effects of norms across gender-groups indicated that young women, more than young men, aimed to ‘have it all’: mirroring their career ambitions to a male career model, while keeping their family aspirations high. Moreover, young women opposed traditional role divisions in the family domain by decreasing their family aspirations in face of norms of lower family involvement or higher career involvement of men. Conversely, in line with traditional gender roles, young men showed lower family aspirations in the face of strong male career norms; and showed increases in their career aspirations when perceiving women to take up more family roles. Young men’s family aspirations were, however, more influenced by new norms prescribing men to invest more in their family, suggesting opportunities for change. Together, these findings show that through social norms, young adults’ gender identity affects aspirations for how to manage the co-presence of their work and family identities. Altering these norms may provide leverage for change to allow both men and women to combine their multiple identities in an enriching way.